Cardiovascular Risk in Chronic Kidney Disease: Role of the Sympathetic Nervous System - Jeanie Park (Cardiology Research and Practice)
Patients with chronic kidney disease are at significantly increased risk for cardiovascular disease and sudden cardiac death. One mechanism underlying increased cardiovascular risk in patients with renal failure includes overactivation of the sympathetic nervous system (SNS). Multiple human and animal studies have shown that central sympathetic outflow is chronically elevated in patients with both end-stage renal disease (ESRD) and chronic kidney disease (CKD). SNS overactivation, in turn, increases the risk of cardiovascular disease and sudden death by increasing arterial blood pressure, arrythmogenicity, left ventricular hypertrophy, and coronary vasoconstriction and contributes to the progression renal disease. This paper will examine the evidence for SNS overactivation in renal failure from both human and experimental studies and discuss mechanisms of SNS overactivity in CKD and therapeutic implications.